TAHAPAN PARTISIPASI MASYARAKAT DALAM PROGRAM KAMPUNGKELUARGA BERENCANA (KB) DI DESA LIMAU MANIS KECAMATAN KAMPAR - Uswatun Hasanah; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The village of Limau Maniswas chosen to be the village for implementing the Kampung KB program which is a program of the central government. The Kampung KB of Limau Manis village was formed in 2017 based on the results of sub-district deliberations. Conditions in the field indicate that the Kampung KB program has been optimal. This is due to high community participation in several stages of community participation. This research aims to determine :1) the stages of community participation in the Kampung KB programof the Limau Manis village 2) the driving factors for the stages of community participation in the Kampung KB program of Limau Manis village. This research uses purposive samping technique with qualitative research type with descriptive case study approach and the required data both primary and secondary data obtained though observation, interviews and documentation then analyzed based on the research problem. The results showed that community participation in the Kampung KB program at the stage of decision making, implemenation stage, evaluation stage and enjoyment stage were at a high level. As for the supporting factors for the high level of community participation in these stages are the support from the community and the support and hard work of the village government, coordinators and cadres of the Kampung KB of Limau Manis village. But the targets of the Kampung KB have not been fully achieved. So the Kampung KB program needs to continue to improve the program so that all the targets that have been set are achieved. In addition, the community must continue to participate in the stage of community participation so that the Kampung KB program in Limau Manis village is always active. Keywords: Participation Stages, Community Participation, Kampung KB